One‐Step C2H4 Purification from Ternary C2H6/C2H4/C2H2 Mixtures by a Robust Metal–Organic Framework with Customized Pore Environment - Wang, Gang‐Ding; Li, Yong‐Zhi; Shi, Wen‐Juan; Hou, Lei; Wang, Yao‐Yu; Zhu, Zhonghua (Angewandte Chemie International Edition, 2022)
One‐step C2H4 purification from ternary C2H6/C2H4/C2H2 mixtures by a single adsorbent is of great industrial significance, but few adsorbents achieve this separation. Herein, we report a robust metal–organic framework (MOF) that possesses methyl‐decorated nonpolar pores and shows one‐step C2H4 purification (purity >99.9 %) from binary C2H6/C2H4 mixtures and ternary C2H6/C2H4/C2H2 mixtures. The methyl groups in pores provide a suitable pore environment to simultaneously enhance the adsorption capacity for C2H2 and C2H6 compared to C2H4. Simulations revealed the multiple interactions between C2H6 or C2H2 molecules and the pore wall, while the interactions with C2H4 molecules are weak and also unfavorable due to the repulsion from methyl groups in pores. The MOF displays high C2H6 and C2H2 uptakes and benchmark C2H6/C2H4 selectivity (2.2), surpassing all of the reported MOFs for one‐step C2H4 purification from ternary C2H6/C2H4/C2H2 mixtures. The combination of nonpolar pore environment and accessible active sites in a metal–organic framework affords benchmark C2H6/C2H4 selectivity and realizes one‐step C2H4 purification from ternary C2H6/C2H4/C2H2 mixtures.